Synthesis of platinum Y-junction nanostructures using hierarchically designed alumina templates and their enhanced electrocatalytic activity for fuel-cell applications - Mahima, Subhramanyam; Kannan, Ramaiyan; Komath, Indulekha; Aslam, Mohammed; Pillai, Vijayarnohanan K. (Chemistry of Materials, 2008)

Y-junction nanostructures of palladium: enhanced electrocatalytic properties for fuel cell reactions - Subhramannia, Mahima; Ramaiyan, Kannan; Aslam, Mohammed; Pillai, Vijayamohanan K. (Journal of Electroanalytical Chemistry, 2009)
Here we demonstrate the utility of hierarchically designed alumina templates for the formation of palladium Y-junction nanostructures through a chemical vapor deposition route. These structures exhibit enhanced electrocatalytic activity for the oxidation of formic acid (up to 1020%) compared to that of platinum Y-junction nanostructures, which could be of immense relevance to portable fuel cell technology, since designing a better electrocatalyst for fuel cell reactions continues to be an important challenge. Apart from the obvious applications in fuel cell electrocatalysis, these Y-junction nanostructures could also act as promising candidates for room temperature hydrogen separation and more importantly as interconnects in molecular scale electronic devices. The present method of fabrication of Y-junction nanostructures using hierarchical alumina templates could be extended to other metallic/semiconducting systems facilitating more general opportunities for such hierarchical designs in nanoelectronics. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: electrocatalysts; fuel cells; Hierarchical structures; Nanostructure; Porous alumina membrane; Y-junctions

Synthesis of Rh-carbon nanotube based heterostructures and their enhanced field emission characteristics - Sathe, Bhaskar R.; Kakade, Bhalchandra A.; Kushwaha, Ajay; Aslam, Mohammed; Pillai, Vijayamohanan K. (Chemical Communications, 2010)
Selective decoration of Rh nanospheres on acid functionalized carbon nanotubes has been demonstrated using Al as a sacrificial substrate. Remarkable field emission has been observed for this heterostructure as a high current density of 170 mu A cm(-2) is generated at an ultra-low threshold of 300 V mu m(-1), compared to much smaller values for Rh nanospheres and carbon nanotubes separately.

Electrochemical unzipping of multi-walled carbon nanotubes for facile synthesis of high-quality graphene nanoribbons - Shinde, Dhanraj B.; Debgupta, Joyashish; Kushwaha, Ajay; Aslam, Mohammed; Pillai, Vijayamohanan K. (Journal of the American Chemical Society, 2011)
Here we report a remarkable transformation of carbon nanotubes (CNTs) to nanoribbons composed of a few layers of graphene by a two-step electrochemical approach. This consists of the oxidation of CNTs at controlled potential, followed by reduction to form graphene nanoribbons (GNRs) having smooth edges and fewer defects, as evidenced by multiple characterization techniques, including Raman spectroscopy, atomic force microscopy, and transmission electron microscopy. This type of ``unzipping'' of CNTs (single-walled, multi-walled) in the presence of an interfacial electric field provides unique advantages with respect to the orientation of CNTs, which might make possible the production of GNRs with controlled widths and fewer defects.

Novel catalyst-free synthesis of vertically aligned silicon nanowire-carbon nanotube heterojunction arrays for high performance electron field emitters - Kale, Vinayak S.; Sathe, Bhaskar R.; Kushwaha, Ajay; Aslam, Mohammed; Shelke, Manjusha V. (Chemical Communications, 2011)
A novel, catalyst-free strategy for the direct synthesis of vertically aligned silicon nanowire-carbon nanotube (SiNW-CNT) heterojunction arrays is presented. Such a heterojunction with the junction area in the nanoscale displays enhanced field emission characteristics at low turn-on field, with a nearly three times increase in the field enhancement factor.

Hysteresis and charge trapping in graphene quantum dots - Kalita, Hemen; Harikrishnan, V; Shinde, Dhanraj B.; Pillai, Vijayamohanan K.; Aslam, Mohammed (Applied Physics Letters, 2013)
We report current hysteresis in response to applied voltage in graphene quantum dots of average diameter 4.5 +/- 0.55 nm, synthesized electrochemically using multiwalled carbon nanotubes. In response to step voltages, transient current decay, characteristic of deep and shallow level charge traps with time constants 186 ms and 6 s, is observed. Discharging current transients indicate charge storage of the order of 100 mu C. Trap states are believed to arise due to the fast physisorption of external adsorbates, which are found to have a significant effect on charge transport and changes the resistance of the prepared device by an order of 3. (C) 2013 American Institute of Physics.

Photophysical and photoconductivity properties of thiol-functionalized graphene-CdSe QD composites - Debgupta, Joyashish; Mandal, Sadananda; Kalita, Hemen; Aslam, Mohammed; Patra, Amitava; Pillai, Vijayamohanan (RSC Advances, 2014)
Graphene-semiconductor QD hybrid nanostructure materials have recently emerged as a new class of functional materials because of their potential applications in solar energy conversion, optoelectronic devices, sensing etc. Here, oleic acid-capped CdSe QDs are attached to -PhSH functionalized graphene by ligand exchange via bonding with the -SH group. The shifting of the G-band and D-band due to structural changes for the attachment of QD with graphene has been evaluated by using Raman spectroscopy. Steady state photoluminescence (PL) and time resolved fluorescence measurements have been employed to understand the electronic interactions between graphene and CdSe QDs. A time resolved fluorescence spectroscopic study has been used to understand the fluorescence dynamics of the photoexcitated CdSe QDs in the presence of graphene. It is evident that the electron transfer occurs from photoexcited QDs to graphene and the electron transfer rate is found to be 12.8 x 10(8) s(-1) for 3.8 nm CdSe QDs. Photoconductivity properties of the graphene-QD device under illumination have been examined and it is to be noted that 2-3 fold increase in the photocurrent is found in this composite device in presence of 1.5 AM solar simulated light. The enhancement of the photocurrent in this hybrid device is found to be suitable for potential applications in optoelectronic and solar cell systems.